Pemanfaatan Minyak Jelantah dalam Pembuatan Sabun Padat Dalam Rangka Peningkatan Kepedulian Masyarakat Terhadap Lingkungan di Desa Karang Tunggal - Hairul Huda; Ahmad Moh Nur; Abdul Kahar; Retno Wulandari; Afifah Vania Faradillah; Tri Agustin; Muhammad Alfian Pahri; Nurhaliza Nurhaliza; Alfani Maulidah Rahmah (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
The large amount of used cooking oil that is thrown into the environment by the community is an urgency that must be addressed. Therefore, it is necessary to handle it efficiently so that it can be used as a product and has economic selling value. Based on the existing urgency as an effort to reduce the impact of environmental pollution, this service was held with the aim of utilizing used cooking oil into solid soap through a saponification process with the help of a strong base such as Sodium Hydroxide (NaOH). The method used was a demonstration of making solid soap which was witnessed by residents of Karang Tunggal village. Apart from preventing the impact of environmental pollution, used cooking oil that is used repeatedly can also harm health, so this service activity is expected to solve this problem and increase public awareness and skills regarding the procedures for processing used cooking oil into solid soap. The results of service activities are training in soap making and distribution of solid soap to the community. It is hoped that service activities can increase understanding and skills in waste management to become more useful and have economic value.